Fate of Fe and Cd upon microbial reduction of Cd-loaded polyferric flocs by Shewanella oneidensis MR-1. (February 2016) - Li, Chenchen; Yi, Xiaoyun; Dang, Zhi; Yu, Hui; Zeng, Tao; Wei, Chaohai; Feng, Chunhua
Abstract: Polyferric sulphate has been widely used for emergent control on incidental release of heavy metals such as Cd to surface water, causing precipitation of Cd-loaded polyferric flocs to the sediment. To date, little is known about whether the dissolution of the flocs in the presence of dissimilatory iron reducing bacteria (DIRB) can occur and how the dissolution influences the fate of Fe and Cd in the sediment. Here, we demonstrated that Shewanella oneidensis MR-1, as representative DIRB, has the ability to reduce the flocs, resulting in the release of Fe 2+ and Cd 2+ to the solution. Batch experiment results showed that the concentrations of Fe 2+ and Cd 2+ reached the maximum values at 48 h and then decreased over the remaining incubation time. The characterizations on the solid phase by the scanning electron microscopy coupled with energy dispersive spectrometer, X-ray diffraction, and X-ray photoelectron spectroscopy technologies revealed the formation of iron minerals such as goethite and magnetite as a consequence of microbial Fe(III) reduction. The newly formed iron minerals played a significant role in re-immobilizing Cd by sorption. These results imply that microbial reduction of polyferric flocs is an important contributor to the transport and transformation of metals in the sediment–water interface. Graphical abstract: Highlights: Shewanella oneidensis MR-1 has the ability to reduce Cd-loaded polyferric flocs. The microbial reduction of flocs induces the release of Fe 2+ and Cd 2+ . The newly formed iron minerals such as goethite and magnetite can re-immobilize Cd.